(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
The study addresses the issue of a comprehensive and systematic approach to the formation and restoration of the visual image of post-war cities in Ukraine. It emphasizes that this process extends far beyond architectural and construction tasks, functioning instead as a strategic, multi-layered project of socio-psychological rehabilitation, cultural identification, and informational resilience. The visual environment of a post-war city is interpreted as an active communicative medium that influences collective memory, emotional well-being, and social cohesion, particularly in societies affected by prolonged military conflict. Special attention is paid to participatory practices as a key foundation for legitimacy, inclusivity, and trust in post-war urban transformation. The research examines contemporary methods of active public engagement, including co-design processes, community-based decisionmaking, and the application of innovative digital tools such as virtual reality (VR). VR technologies are analyzed as instruments for project visualization, inclusivity testing, risk mitigation, and the achievement of social consensus prior to implementation, thereby democratizing the design process and reducing conflict between stakeholders. The paper proposes a comprehensive, multi-phase program that integrates long-term strategic planning instruments, such as the development of urban master plans, municipal design codes, and visual regulation frameworks, with tactical and operational solutions. These include localized design interventions in specific urban areas (streets, squares, small public spaces, courtyards), rapid urban improvement measures, and the creation of exemplary “postcard” views and selfie zones. Such interventions are considered not merely as aesthetic enhancements, but as tools for shaping a positive visual narrative, strengthening urban branding, and supporting psychological recovery during and after the conflict. Using Kharkiv as a case study, the research analyzes practical strategies for maintaining and preserving a positive visual image of the city under conditions of active hostilities. These strategies include the organization of safe festive, cultural, and memorial events, as well as temporary and adaptive spatial interventions, which function as mechanisms for sustaining community morale, reinforcing collective identity, and counteracting narratives of destruction. The study concludes that post-war recovery presents a unique opportunity not only to rebuild damaged infrastructure, but to achieve a qualitative transformation of the urban environment. This transformation aims to produce cities that are more humane, resilient, visually coherent, and socially inclusive, grounded in European values, cultural continuity, and active civic participation. The findings contribute to the interdisciplinary discourse on post-conflict urbanism and may serve as a methodological framework for policymakers, urban planners, architects, and local communities involved in the reconstruction of war-affected cities.